34. KNOWLEDGE AND PRACTICES OF STANDARD PRECAUTIONS AMONG HEALTHCARE WORKERS AT AN GIANG EYE - EAR NOSE THROAT - DENTAL HOSPITAL IN 2024 (Vietnam Journal of Community Medicine, 2025)
Objective: To describe the current status of knowledge and practice of standard prevention among healthcare workers at An Giang Eye - Ear, Nose, Throat - Odonto - Stomatology Hospital.Subjects and methods: A cross-sectional descriptive study was conducted among 120 healthcare workers from both clinical and paraclinical departments of An Giang Eye - Ear, Nose, Throat - Odonto - Stomatology Hospital.Results: The overall proportion of healthcare workers achieving adequate knowledge scores on standard precautions was 89.7%, the lowest was in handling textiles (79.4%), the highest was in waste management (90%), p < 0.001. The rate of health workers with good knowledge of standard prevention was 90.8%. The overall proportion of standard precaution practice scores was 66.7%, the lowest was in environmental surface cleaning practice (49.5%), the highest was in glove removal practice (92%), p < 0.001. The rate of healthcare workers practicing standard precautions well was 42.5%. Univariate analysis showed that factors related to health care workers’ standard precautions included: age (OR = 7.39; p = 0.007), occupation (OR = 23.4; p < 0.0001), professional level (OR = 9.85; p = 0.002), training in infection control (OR = 29.5; p < 0.001) and good knowledge of standard precautions (OR = 5.53; p = 0.01). The study results showed that An Giang Eye - Ear, Nose, Throat - Odonto - Stomatology Hospital needs to strengthen training programs and enhance supervision measures to improve knowledge and standard precaution practices among healthcare workers.
Keywords: Knowledge; practice; standard precautions; healthcare workers.